Trabalhadores, empregadores e estado brasileiro: revisitando os conflitos de greve na história constitucional brasileira entre 1935 e 1937 - Silva, Danillo Lima da (2021)
The concept of strike comes from a non-linear historical process of clashes that mediate the relationship between Law and Politics, class disputes and the role of the State. As a legal and social phenomenon, it is complex and certainly it is a key to understanding Brazilian constitutional experiences. During the Vargas government, the regulation of labor rights, unions and social issues became a special agenda. The present work aims to analyze, from a historical point of view, how the strike was legally reformulated within the practice of institutionality before the criminalization that took place in 1937. The objective is achieved through the analysis of the narratives constructed in the judgments of the National Labor Council (Conselho Nacional do Trabalho - CNT), between 1935 – especially the National Security Law No. 38, of April 4, 1935, context of the communist uprising – and 1937, when it was granted the Federal Constitution. As for the methodology, the study had as its object primary sources, selected from the mapping of processes in the CNT archive. The search criteria were the theme of the strike in the selected time frame. In this situation, it was possible to identify eleven processes. The analysis focused on the speeches of the actors involved and the decisions produced by the CNT, comparing them with the context, legislation, doctrine and bibliography about the time. It is possible to conclude that period is marked by political and social tensions, intense legislative production with labor regulation and that strike movements were treated as police cases by the Executive Branch. The CNT, on the other hand, took a formalistic stance, often limiting itself to the formal aspects of the process. However, after the communist uprising of 1935, the strike movement began to be considered as a political crime that generated social disorder, and should be faced from the perspective of the National Security Law at the time. Therefore, the strike is a key to reading the Brazilian constitutional history, especially because it allows us to understand how governments, legal texts and institutions dialogue with the expectations of the people and how they are socially inserted